Use of mulberry leaf meal in fattening diets for rabbits: a comprehensive approach from animals to consumers - I. Biasato; M. Renna; G.L. Cerutti; F. Maccagno; C. Lussiana; I. Ferrocino; S. Bellezza Oddon; C. Caimi; G. Xiccato; A. Trocino; A. Pauciullo; A. Brugiapaglia; et al. (Animal)
Mulberry leaf meal (MLM) may act as a promising, alternative feed ingredient for rabbit farming, due to its good nutrient digestibility and high fibre content. Therefore, this study evaluated the effects of the inclusion of MLM in the fattening diet of rabbits on their productive performance, caecal microbiota, genotoxicity, and meat quality and consumer acceptance. A total of 480 crossbred rabbits weaned at 45 days of age were allotted to two dietary treatments (30 replicate cages/treatment, 8 rabbits/cage). During the post-weaning phase (45–63 days of age), both groups were fed the same commercial feed; during the fattening phase (64–88 days of age), two isonitrogenous, isolipidic and isoenergetic diets were fed: (1) control diet (C) and (2) MLM diet (10% MLM). During fattening, the MLM rabbits displayed higher daily feed intake (DFI) and feed conversion ratio than the C ones (P < 0.05), with higher DFI in the MLM than in the C group over the whole trial (P < 0.01). At slaughter, the relative weight of the liver was lower in MLM than in C rabbits (P < 0.05). The caecal microbiota and Sister Chromatid Exchange frequency were not significantly influenced by MLM inclusion (P > 0.05). The Longissimus thoracis et lumborum (LTL) yellowness and saturation indexes were lower in the MLM than in the C group (P < 0.05), and the former also showed a lower ether extract in the LTL when compared to the latter rabbits (P < 0.01). The proportion of the majority of fatty acids did not differ according to the diets. Only stearic and α-linolenic acids rates were lower and higher, respectively, in the thighs of MLM-fed rabbits (P < 0.05). At the consumer test, the MLM meat was penalised for being “too dry” and “too bland” in flavour when compared to the C meat. In conclusion, dietary MLM inclusion in the fattening phase may impair the feed conversion of rabbits, without impairing their final weight, carcass traits, caecal microbiota, and genome stability. Paler, leaner, and α-linolenic-enriched meat can also be obtained, which however may be potentially perceived by consumers as less juicy and flavoured when compared to conventional meat.